Multiple lipoleiomyoma of the uterine cervix in premenopausal woman: a case report - Singh, Smita; Kumar, Rakesh; Jyoti, Divya; Agarwal, Kiran (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Leiomyoma is a most frequently occurring benign mesenchymal tumor of monoclonal origin arising from the smooth muscle cells of the uterus. There are different subtypes of leiomyoma based on their morphological features. Lipoleiomyoma is a rare distinct variant of leiomyoma with a heterogenous cut surface comprising soft yellow areas of fatty tissue intermixed with firm rubbery areas of smooth muscle tissue. We report a case of a 35-year-old multipara premenopausal woman who presented with abdominal distension and chronic pelvic pain. Clinical examination gave an initial impression of a teratoma. Multiple large heterogenic cervical masses of varying sizes were noted on ultrasonography. Histopathological examination of the surgical resection specimen revealed multiple mature lipoleiomyomas. This case report is unique due to its occurrence in premenopausal women and its location in the cervix.